Critical Issues for the Development of Sustainable E-health Solutions - Wickramasinghe, Nilmini.; Wickramasinghe, Nilmini.; Bali, Rajeev.; Bali, Rajeev.; Suomi, Reima.; Suomi, Reima.; Kirn, Stefan.; Kirn, Stefan. (Healthcare Delivery in the Information Age,, 2012)
Critical Issues for the Development of Sustainable E-Health Solutions Nilmini Wickramasinghe, editor    Health care companies want to deliver their services with greater efficiency and cost-effectiveness. Consumers want services that are effective, responsive, convenient, and worth the cost. In response to these demands, web-based and other electronic technologies are revolutionizing health care services. Critical Issues for the Development of Sustainable E-Health Solutions surveys this rapid transformation as it is occurring worldwide.   Focusing on new applications in consumer-centered health care in North America, Europe, and Asia, the book demonstrates how electronic innovations can balance business objectives (e.g., low cost, improved performance management) while attending to consumer needs (e.g., access, quality, and value). Keeping technical jargon to a minimum, chapter authors dissect the impact of e-solutions on both sides of the health care system, and the keys to successful adaptation and sustainability. Facilitators and obstacles to IT changeovers based on economic, cultural, and other factors are identified in detail. And the book warns realistically against the pitfalls of designing and implementing tech-based platforms in systems not yet ready to make such changes.   A sampling of topics covered: A strategic model for health care IS design. Online discussion forums as a means of peer support. Improving web accessibility for disabled people. Knowledge management: often neglected yet crucial to e-health. Business models for electronic health care services: examples from Germany. A comprehensive approach to the IT-clinical practice interface.   With its wide scope of innovative ideas, Critical Issues for the Development of Sustainable E-Health Solutions is a path-breaking text for health care administrators and researchers in health care management, health policy, and health services.